2016
DOI: 10.1007/s00170-016-8970-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of hot embossing stamps with conformal cooling channels for microreplication

Abstract: Hot embossing stamp fabricated from aluminumfilled epoxy resin can be employed for short-run productions. However, the cooling time is much longer compared to metallic stamps due to poorer thermal conductivity. Therefore, developing a hot embossing stamp with high cooling efficiency is an important issue. In this study, three different coolingchannel layouts were employed to fabricate hot embossing stamps using rapid prototyping and rapid tooling techniques. Effects of different hot embossing stamps on the coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…A low-cost wax injection mold with high cooling efficiency was developed [ 16 , 17 ]. A hot embossing stamp with CCCs for microreplication was developed [ 18 ]. Results showed that the reduction in cooling time of about 92% was obtained when a hot embossing stamp had conformal cooling channels compared to the hot embossing stamp, which has conventional cooling channels.…”
Section: Introductionmentioning
confidence: 99%
“…A low-cost wax injection mold with high cooling efficiency was developed [ 16 , 17 ]. A hot embossing stamp with CCCs for microreplication was developed [ 18 ]. Results showed that the reduction in cooling time of about 92% was obtained when a hot embossing stamp had conformal cooling channels compared to the hot embossing stamp, which has conventional cooling channels.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Kuo and Wang 45,46 proposed a plasma surface modification method to manufacture precision micro-hot embossing moulds with high surface finishes.
Figure 6.Schematic diagrams of manufacturing hot embossing stamp: (a) Master model; (b) Designing cooling channels; (c) Pouring aluminium-filled epoxy resin; (d) Removal of mould frame; (e) Removal of master model; (f) Removal of cooling channels. 41
…”
Section: Recent Investigations Of Epoxy Toolingmentioning
confidence: 99%
“…Figure 6. Schematic diagrams of manufacturing hot embossing stamp: (a) Master model; (b) Designing cooling channels; (c) Pouring aluminium-filled epoxy resin; (d) Removal of mould frame; (e) Removal of master model; (f) Removal of cooling channels 41. …”
mentioning
confidence: 99%
“…It was found that the hybrid tools withstand the high mechanical and thermal loads which occur during hot aluminum extrusion. However, the structural strength of the injection molding tooling with the conformal cooling channels will reduce signi cantly [12][13][14][15]. Figure 1 shows the schematic illustration of a cooling channel cell under high injection pressure.…”
Section: Introductionmentioning
confidence: 99%